Observations of f-region critical frequency variation over Batu Pahat, Malaysia during low solar activity - Abdullah, Sabirin (2011)
Wireless radio in the HF band still uses the ionospheric layer as the main medium for communication. Critical frequencies are important parameters of the ionosphere. Due to the activities of the sun, the critical frequency varies diurnally, following the pattern of day and night. The critical frequency for the Parit Raja station is determined using an ionosonde at latitude 1° 52' N and longitude 103° 48' E which is close to the geomagnetic equator at geographic latitude 5° N. This work analyses the dependence of the critical frequency during the solar minimum of Solar Cycle 23. The median critical frequency value is used to develop a model using regression and polynomial approaches because it is more accurate than using average values. From the observations, the critical frequency observed in 2005 is the highest, corresponding to a higher sunspot number of between 11 and 192. In contrast, the critical frequency is lower in 2007 due to the decrease in the sunspot number of between 11 to 63. The general trend of the daily critical frequency is 6.8 MHz to 12.0 MHz from 00:00 to 17:30 UTC and decreasing to 7.0 MHz from 18:00 to 23:00 UTC. The average value of the critical frequency for 2005 to 2007 is 7.5 MHz, with a minimum of 1.8 MHz and a maximum of 11.0 MHz. In addition, the daily observed virtual height for the F-layer is 200 to 480 km except during the months of January, February, November and December, during which it is much higher up to 550 km. The Parit Raja model showed good agreement for the 3rd degree polynomial fitted between the measured values. This model can be used as a reference ionospheric profile over southern Malaysia.